Deposition characterisation and process window development for plasma sprayed thermal barrier coatings - Ng, Heong Wah. (2010)
The process of plasma spray deposition is capable of producing tough and hardwearing coatings of various materials that can be used for thermal barriers, hard surface protection against wear, erosion and corrosion and special tailored properties such as functionally graded materials. Industries or applications employing this technology are paper, earth moving and harsh service equipment, aircraft landing gears and engines MRO (Maintenance Repair Overhaul), biomedical implants, fuel cells and embedded sensors. The main issues in spraying have been in coating thickness control especially in spraying of three dimensionally complex components which have concave or convex curvatures. When spraying onto curved surfaces such as on many engineering components, the molten droplets impact in a spray cone pattern such that many droplets impact at oblique angles. The subsequent splats will be flattened into an elliptical shapes and the overall thickness deposit is uneven. To investigate this problem, a computational framework for predicting three-dimensional physically realistic plasma sprayed deposits is described in this presentation. A computer program constructs three dimensional profiles representing the deposit build up after sustained spraying with the torch spraying at the same spot. The predicted deposition volumes and thicknesses for different substrate inclinations were found to be in good agreement with experimentally sprayed deposits. This procedure is extremely useful for the plasma spray industries as it reduces the cost of spraying first cut or making the first trial spray of the new shape of turbine blades or complicated shaped part. It reduces the cost of spray booth time, part and powder cost, the manpower cost to perform trial and error spraying. The plasma spray process is influenced by many process control parameters, as much as 20 separate parameters control the coating formation. Generally, process control is to ultimately control the temperature and velocity of particles which impact on the substrate. A process map which indicate the best control location for optimum operation is derived by simulation and experimentation in the paper.